Outcomes of secondary solid tumor malignancies among patients with myeloma: A population‐based study. Issue 4 (19th November 2018) - Barth, Peter; Castillo, Jorge J.; Olszewski, Adam J.
Abstract: Background: Therapeutic advances have extended survival for patients with myeloma, who may develop secondary cancers. Methods: Using the population‐based Surveillance, Epidemiology, and End Results registry (2004‐2015), the authors examined the characteristics, overall and cause‐specific survival, and cumulative incidence function of cancer‐related death among patients with myeloma with secondary cancers of the breast, prostate, lung, colon/rectum, or bladder or melanoma. Each patient was matched based on age, sex, race, and year of diagnosis to 50 controls from a general population who were diagnosed with the index cancer. Results: Patients with myeloma with breast, prostate, or lung cancer were more commonly diagnosed at an early stage, whereas the stage distribution did not differ significantly among patients with melanoma, colorectal cancer, or bladder cancer. For all studied cancers except those of the lung, overall mortality was significantly higher among patients with myeloma compared with controls (hazard ratios, 1.84‐2.81). However, the cumulative incidence function of cancer‐related death did not differ (subhazard ratios, 0.84‐0.99) and was surpassed by myeloma‐related deaths (23% to 35% at 5 years). In patients with lung cancer, cancer‐related mortality was uniquely lower among patients with myeloma (subhazard ratio, 0.59; 95% confidence interval, 0.52‐0.68), even after adjustment for stage of disease. There was no significant difference noted with regard to noncancer deaths for any studied solid tumor. Use of surgery (evaluated in patients with nonmetastatic tumors, and in addition matched by disease stage) did not differ between cases and controls, except for fewer prostatectomies being noted among patients with myeloma (odds ratio, 0.56; 95% confidence interval, 0.42‐0.74). Conclusions: The results of the current study support curative treatment approaches to secondary cancers among patients with myeloma while highlighting the need for ongoing active myeloma management. Abstract : Among patients with myeloma who are diagnosed with common solid tumors, the risk of cancer‐related death is similar to that of the general population of patients with the same cancers. Mortality because of myeloma exceeds the risk of cancer‐related death in the majority of settings, highlighting the need for ongoing myeloma surveillance in addition to age‐appropriate cancer screening.